The changing academic library : - Budd, John M. (Association of College and Research Libraries, 2005)
Budd (affiliation not cited) examines current practices in academic libraries within the broader context of educational needs, economic realities, and the nature of complex organizations. Each of 12 chapters concludes with some questions to provoke discussion. Sample topics include scholarly communication, electronic information, and governance issues.